Hubungan Kedisiplinan Dengan Hasil Belajar Siswa Dalam Pembelajaran IPS Kelas VIII SMP YPI Baiturrahman Ngoro Mojokerto - Ma’una Nasution, Isnaini Ila; Prasetyo, Ketut; Marzuqi, Muhammad Ilyas (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the relationship between discipline and student learning outcomes in social studies learning for class VIII SMP YPI Baiturrahman Ngoro Mojokerto. This study uses a quantitative method with a correaltion approach, based on the discipline theory of Tu’u (2004). Data were collected through questionnaires and documentation, then analyzed using the SPSS version 24 program. The research sample consisted of 32 class VIII students. The results showed a fairly strong relationship between discipline and student learning outcomes (correlation value r = 0,405). The relationship between discipline and student learning outcomes in social studies learning for class VIII SMP YPI Baiturrahman Ngoro Mojokerto was proven to be statistically significant (2,425 2,042). In conclusion, there is a positive relationship between discipline and learning outcomes. Students who are more disciplined tend to get better grades.